2017
DOI: 10.1099/ijsem.0.001755
|View full text |Cite
|
Sign up to set email alerts
|

Introducing EzBioCloud: a taxonomically united database of 16S rRNA gene sequences and whole-genome assemblies

Abstract: The recent advent of DNA sequencing technologies facilitates the use of genome sequencing data that provide means for more informative and precise classification and identification of members of the Bacteria and Archaea. Because the current species definition is based on the comparison of genome sequences between type and other strains in a given species, building a genome database with correct taxonomic information is of paramount need to enhance our efforts in exploring prokaryotic diversity and discovering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
3,882
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 6,122 publications
(4,138 citation statements)
references
References 23 publications
13
3,882
0
20
Order By: Relevance
“…fusiformis NBRC 15717 T , and 99.60% with L. mangiferihumi M-GX18 T , as analyzed using the EzBioCloud Web server identity tool (9). …”
Section: Genome Announcementmentioning
confidence: 99%
“…fusiformis NBRC 15717 T , and 99.60% with L. mangiferihumi M-GX18 T , as analyzed using the EzBioCloud Web server identity tool (9). …”
Section: Genome Announcementmentioning
confidence: 99%
“…In sodium bicarbonate-buffered medium (1), growth occurred at 1% to 13% (wt/vol) NaCl (optimum, 8% NaCl), pH 8.0 to 10.5 (optimum, 9.0), and 15°C to 45°C (optimum, 35°C). Pairwise sequence similarities of 16S rRNA genes were calculated using a global alignment algorithm implemented by applying the EzBioCloud server (2). The result revealed that YSP-3 had the highest 16S rRNA gene sequence similarities with Bacillus aurantiacus K1-5 T (97.9  %) and Bacillus populi FJAT-45347 T (97.01%).…”
Section: Announcementmentioning
confidence: 99%
“…The sequences of the 16S rRNA marker genes were obtained from the RAST annotations of UMA81211 and UMA81212 and showed 98.67% and 98.27% similarity to Alloscardovia macacae M8, respectively (3, 4). The next highest similarity scores were for Alloscardovia criceti DSM17774 (UMA81211, 96.54%; UMA81212, 96.31%) and Alloscardovia omnicolens DSM21503 (UMA81211, 96.54%; UMA81212, 95.93%) (3, 5).…”
Section: Genome Announcementmentioning
confidence: 99%